2021
DOI: 10.3390/cells10123373
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Differences in Monocyte Subsets and Cytokine Pattern during Acute COVID-19—A Prospective Observational Longitudinal Study

Abstract: The COVID-19 pandemic drastically highlighted the vulnerability of the elderly population towards viral and other infectious threats, illustrating that aging is accompanied by dysregulated immune responses currently summarized in terms like inflammaging and immunoparalysis. To gain a better understanding on the underlying mechanisms of the age-associated risk of adverse outcome in individuals experiencing a SARS-CoV-2 infection, we analyzed the impact of age on circulating monocyte phenotypes, activation marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Our group previously documented similar trends of serum IL-6 among critically ill patients receiving immunomodulatory therapies [18,32]. Other studies have demonstrated that persistently elevated serum IL-6 levels during COVID-19 are independently associated with in-hospital mortality, and rises of serum IL-6, IL-8 and TNF-α are probably age-dependent, translating to poorer outcomes among the elderly [22,24,33]. Pro-inflammatory cytokine responses in blood were detectable for ≥3 weeks after SARS-CoV-2 infection [34].…”
Section: Previous Literature Findingssupporting
confidence: 73%
“…Our group previously documented similar trends of serum IL-6 among critically ill patients receiving immunomodulatory therapies [18,32]. Other studies have demonstrated that persistently elevated serum IL-6 levels during COVID-19 are independently associated with in-hospital mortality, and rises of serum IL-6, IL-8 and TNF-α are probably age-dependent, translating to poorer outcomes among the elderly [22,24,33]. Pro-inflammatory cytokine responses in blood were detectable for ≥3 weeks after SARS-CoV-2 infection [34].…”
Section: Previous Literature Findingssupporting
confidence: 73%
“…Although highly speculative at this time, the notion of early SARS-CoV-2 infection bearing on immunobiography and increasing inflammaging may have some merit. It was found that severe COVID-19 is associated with higher levels of proinflammatory cytokines leading from inflammaging to immunoparalysis ( Muller and Di Benedetto, 2021 , Pirabe et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have described the association of higher age with more severe COVID‐19 disease outcomes [27]. Age‐associated changes in the immune response such as altered cytokine responses in elderly patients have been shown to contribute to more severe COVID‐19 [28]. Interestingly, in aged mice, upregulation of CD86 is reduced after TLR2 and influenza‐induced stimulation [29].…”
Section: Discussionmentioning
confidence: 99%